The influence of aging on shape memory effect in Ti‑50.7at.%Ni and Ti‑51.7at.%Ni single crystals - Timofeeva, Ekaterina E.; Zherdeva, Maria V.; Panchenko, Elena Yu; Eftifeeva, Anna S.; Surikov, Nikita Yu; Tagiltsev, Anton I.; Chumlyakov, Yuri I.; Marchenko, Ekaterina S. (Shape memory and superelasticity)
The shape memory effect (SME) during stressassisted thermal cycles under compressive load in [001]-oriented Ti-50.7at.%Ni and Ti-51.7at.%Ni single crystals aged at 823 K for 1 h has been studied. Ti3Ni4 particles with a diameter of 300–400 nm were precipitated with volume fractions of 11 and 22% and interparticle distances of 300–500 nm and 50–150 nm, respectively. In quenched single crystals, the SME parameters were determined by the transformation type (thermal-induced martensitic transformation (MT) or strain glass transition). In contrast, the SME parameters of aged single crystals were determined by the volume fraction of particles and interparticle distances. Differing volume fractions of particles and interparticle distances led to different temperatures ( M0s ) for the formation of B19′-martensite, different strain (εrev), different dependences of the interval of forward MT ( Δσ1) and thermal hysteresis ( ΔT1= Aσf−Mσs and ΔT2= Aσs−Mσf) on applied stresses, and changes in the morphology of martensite crystals. Practically, these differences do not affect the stresses (σmin and σmax) required to achieve the minimum strain and maximum reversible strain (εrev) and strain growth coefficient (dεrev/dσ). The influence of aging on the dependence of the SME parameters on the chemical composition was analysed in comparison with quenched crystals.